To teach or not to teach? That is the question! – gender, work and human education in Subsequent technical Courses (Research, Society and Development, 2022)
The text discusses the teaching of the gender theme in high school technical courses offered subsequently at the Federal Institute of Alagoas (Instituto Federal de Alagoas - Ifal), which is a result of an exploratory study with a qualitative approach, the exhibition systematizes a set of data obtained during research carried out in the Postgraduate Program in Professional and Technological Education at Ifal between 2019 and 2021 and which recorded the understanding of a group of professors about the concept of gender and their perception of the relationship between the teaching of the subject and the professional training of high school technicians. In order to highlight some contradictions that permeate the training processes of high school technicians, we discuss how the school curriculum and educational praxis, mediated by the individual understanding of teachers about gender, distance themselves from the training proposal of Professional and Technological Education and from what is expected as a professional profile of the graduate. Anchored in the concept of gender enunciated by Joan Scott, by the documental analysis and by the diagnostic survey, we identified that a partial understanding of the gender concept, which is not conceived in its relationship with the world of work, makes the teaching of the subject to be treated as something of lesser importance for professional training. This perspective is manifested by the absence of the theme in the school curricula of the subsequent courses and by the absence of spaces for qualified educational work carried out from the human sciences and that is directed towards integral formation and human emancipation.